Determinants of habitat use and community structure of rodents in northern shortgrass steppe - Stapp, Paul T., author; Van Horne, Beatrice, advisor; Bjostad, Louis Benjamin, committee member; Wiens, John A., committee member; Wunder, Bruce A., committee member (Colorado State University. Libraries, 1996)
Patterns of distribution and abundance of small mammals reflect the responses of individuals to the spatial and temporal availability of resources and abiotic conditions, as well as interactions with conspecifics and other species. I examined habitat selection of two rodents, the deer mouse (Peromyscus maniculatus) and the northern grasshopper mouse (Onychomys leucogaster), on shortgrass steppe in north-central Colorado. Both species consume arthropods when these resources are plentiful, but grasshopper mice prey on other rodents and thus may have both competitive and predatory effects on deer mice. To examine these interactions, I conducted a removal experiment to determine the effect of grasshopper mice on microhabitat use, diet, and abundance of deer mice, and an odor-response experiment to determine whether olfactory cues mediate interactions between these species. Deer mice preferred shrubs at both individual and population levels, presumably to reduce predation risk. Mice oriented movements toward shrubs and traveled under shrubs more often than expected based on the density of shrubs on study plots. Population density also increased with increasing shrub density and aggregation. The response of mice to shrub cover was non-linear. Thresholds in the selective use of shrubs, movement patterns, and abundance occurred over a narrow range of shrub cover where shrubs were most aggregated, underscoring the importance of both shrub density and dispersion. Mice tended to accumulate in areas where their movements were most tortuous, suggesting that it is possible to generate testable predictions about patterns of abundance from individual movements. In contrast, grasshopper mice showed no affinity for shrub microhabitats, and instead oriented movements towards rodent burrows and disturbances created by pocket gophers (Thomomys talpoides). Results from pitfall trapping in different microhabitat types suggested that grasshopper mice used gopher mounds and burrows because of the concentration of insect prey in these microhabitats. The abundance of these microhabitats also was a better predictor of grasshopper-mouse abundance than were broad-scale, qualitative descriptors of macrohabitat type. The significance of these microhabitats across scales demonstrates the importance of spatial and temporal availability of prey to grasshopper mice. Even though grasshopper mice and deer mice show different habitat affinities, grasshopper mice may affect the surface activity and abundance of deer mice in areas where they co-occur. Deer mice decreased in number throughout the removal experiment on both control and removal sites, but the decline was greatest on controls, where grasshopper-mouse numbers increased. No shifts in microhabitat use were detected on removal sites, but deer mice increased their use of shrubs on control sites when grasshopper mice were most abundant. Because diets of deer mice did not differ between control and removal sites during the experiment, grasshopper mice apparently influenced the behavior and populations of deer mice through predation or interference rather than resource competition. Increases in the abundance of granivorous rodents on removal sites support this conclusion, and suggest that grasshopper mice, when abundant, can impact the composition of local assemblages on shortgrass steppe. However, if deer mice actively avoid contact with grasshopper mice, it is unlikely that this interaction is mediated by olfactory cues. When presented with odors of grasshopper mice, harvest mice, and clean cotton, deer mice showed no avoidance of grasshopper-mouse odors, regardless of season, sex or reproductive condition of respondents, or history of contact with grasshopper mice.
Keywords: Peromyscus -- Habitat -- Colorado; Northern grasshopper mouse -- Habitat -- Colorado; Grassland ecology -- Colorado